Capturing LTA(4) hydrolase in action: Insights to the chemistry and dynamics of chemotactic LTB(4) synthesis - Stsiapanava, Alena (Proc Natl Acad Sci U S A, 2017)
Human leukotriene (LT) A(4) hydrolase/aminopeptidase (LTA(4)H) is a bifunctional enzyme that converts the highly unstable epoxide intermediate LTA(4) into LTB(4), a potent leukocyte activating agent, while the aminopeptidase activity cleaves and inactivates the chemotactic tripeptide Pro-Gly-Pro. Here, we describe high-resolution crystal structures of LTA(4)H complexed with LTA(4), providing the structural underpinnings of the enzyme’s unique epoxide hydrolase (EH) activity, involving Zn(2+), Y383, E271, D375, and two catalytic waters. The structures reveal that a single catalytic water is involved in both catalytic activities of LTA(4)H, alternating between epoxide ring opening and peptide bond hydrolysis, assisted by E271 and E296, respectively. Moreover, we have found two conformations of LTA(4)H, uncovering significant domain movements. The resulting structural alterations indicate that LTA(4) entrance into the active site is a dynamic process that includes rearrangement of three moving domains to provide fast and efficient alignment and processing of the substrate. Thus, the movement of one dynamic domain widens the active site entrance, while another domain acts like a lid, opening and closing access to the hydrophobic tunnel, which accommodates the aliphatic tale of LTA(4) during EH reaction. The enzyme–LTA(4) complex structures and dynamic domain movements provide critical insights for development of drugs targeting LTA(4)H.